2018
DOI: 10.1111/bph.14224
|View full text |Cite
|
Sign up to set email alerts
|

The novel μ‐opioid receptor agonist PZM21 depresses respiration and induces tolerance to antinociception

Abstract: Background and PurposePZM21 is a novel μ‐opioid receptor ligand that has been reported to induce minimal arrestin recruitment and be devoid of the respiratory depressant effects characteristic of classical μ receptor ligands such as morphine. We have re‐examined the signalling profile of PZM21 and its ability to depress respiration.Experimental ApproachG protein (Gi) activation and arrestin‐3 translocation were measured in vitro, using BRET assays, in HEK 293 cells expressing μ receptors. Respiration (rate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
157
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(181 citation statements)
references
References 27 publications
20
157
2
Order By: Relevance
“…They also showed that PZM21 had substantially lower efficacy than DAMGO, using a BRET-based assay to detect the dissociation of G αi1 and G γ2 (Hill et al, 2018). Our data are also consistent with another recent publication, which using conformational biosensor binding to the purified μ receptor, showed that PZM21 had lower efficacy than morphine, or fentanyl, two opioids used clinically (Livingston et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…They also showed that PZM21 had substantially lower efficacy than DAMGO, using a BRET-based assay to detect the dissociation of G αi1 and G γ2 (Hill et al, 2018). Our data are also consistent with another recent publication, which using conformational biosensor binding to the purified μ receptor, showed that PZM21 had lower efficacy than morphine, or fentanyl, two opioids used clinically (Livingston et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…A recent report showed that PZM21 induced respiratory depression similar to that evoked by morphine (Hill et al, 2018), which is in contrast to the earlier report describing this biased agonist (Manglik et al, 2016).…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…where ligand potency increased as a function of aliphatic group size (Figure 6c). One compound in particular, propyl substituted FD-3, retained partial-agonist properties comprising a mid-nanomolar EC 50 with a maximal coupling efficiency that is approximately 67% that of morphine [16] and comparable to the Figure 6c). Taken together with our prior mutational analysis, these experiments suggest that the n-aniline ring is required for fentanyl mediated β-arrestin, but not Gi coupling, and this effect is mediated through an interaction with M153 3.36 .…”
Section: Fentanyl's N-aniline Ring Mediates β-Arrestin Signalingmentioning
confidence: 61%